2021
DOI: 10.3389/fpubh.2021.699675
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Symptoms in Magnetic Resonance Imaging Personnel: A Multi-Center Study in Italy

Abstract: Introduction: Magnetic Resonance Imaging (MRI) personnel have significant exposure to static and low-frequency time-varying magnetic fields. In these workers an increased prevalence of different subjective symptoms has been observed. The aim of our study was to investigate the prevalence of non-specific subjective symptoms and of “core symptoms” in a group of MRI personnel working in different centers in Italy, and of possible relationships with personal and occupational characteristics.Methods: The occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This exposure leads to the onset of transient symptoms. Dizziness, vertigo, visual disturbances, nystagmus, and metallic taste were the most frequently reported symptoms induced by worker movements in the fringe field [4]. Many studies highlighted the occurrence of transient symptoms, often defined as sensory effects [5]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…This exposure leads to the onset of transient symptoms. Dizziness, vertigo, visual disturbances, nystagmus, and metallic taste were the most frequently reported symptoms induced by worker movements in the fringe field [4]. Many studies highlighted the occurrence of transient symptoms, often defined as sensory effects [5]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…When the currents are strong enough, they can cause effects on the central nervous system (CNS) and stimulate peripheral nerves. Recent studies have reported transient symptoms induced by workers' movements [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%